ANALISIS KESULITAN MAHASISWA DALAM MENYELESAIKAN SOAL BILANGAN REAL - Siregar, Nur Fauziah (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2018)
This study discusses the problems faced by students in solving real number problems and analyzing the causes. This type of research is qualitative research using descriptive analysis. Data collection methods used in this study are documentation of UTS results and interviews. The results of this study indicate that the difficulties experienced by students in completing real number problems: (1) difficulties in understanding the concept and applying it, (2) difficulty manipulating the numbers and symbols. Errors made by students to solve real number problems are an explanation of the difficulties experienced by students. The factors that cause students to overcome the problems of the basic concept of real numbers, students are still having difficulty in understanding the use of the concept of real numbers, are less careful in solving problems so they are wrong in translating symbols, student learning patterns that are not good are not supported by learning resources adequate material and difficult to repair.